Power to the poor : black-brown coalition and the fight for economic justice, 1960-1974 - Mantler, Gordon K. (Gordon Keith), 1972- (Justice, power, and politics., 2013)
The Poor People's Campaign of 1968 has long been overshadowed by the assassination of its architect, Dr. Martin Luther King Jr., and the political turmoil of that year. In a major reinterpretation of civil rights and Chicano movement history, the author demonstrates how King's unfinished crusade became the era's most high-profile attempt at multiracial collaboration and sheds light on the interdependent relationship between racial identity and political coalition among African Americans and Mexican Americans. The author argues that while the fight against poverty held great potential for Black-brown cooperation, such efforts also exposed the complex dynamics between the nation's two largest minority groups.